Culturable bacterial phylogeny from a shallow water hydrothermal vent of espalamaca (Faial, Azores) reveals a variety of novel taxa - Rajasabapathy, Raju; Mohandass, Chellandi; Colaco, Ana; Dastager, Syed Gulam; Santos, Ricardo Serrao; Meena, Ram Murti (Current Science, 2014)
Phylogenetic diversity of the 16S rRNA gene associated with the domain bacteria was examined at the level of operational taxonomic units (OTUs) using the rarefaction analysis from a newly identified shallow water hydrothermal vent, Espalamaca in the Azorean Island Faial (Horta), North Atlantic Ocean. Diluted sea water nutrient agar amended with metals manganese, lead, iron and element sulphur, could help in retrieving highest OTUs (95) from the vent and 39 OTUs from nonvent. Molecular tools implemented on bacterial census indicated the occupancy of gamma-Proteobacteria by 55.78%, alpha-Proteobacteria by 21.05% and 12.63% of Bacteroidetes in the total population. Occurrence of novel species maximized with alpha-Proteobacteria (11/20) followed by Bacteroidetes (5/12) signified the necessity of studying these groups to strengthen the biodiversity database. Shannon index (H') and the Chao I richness estimator illustrated a strong bacterial community in the venting area. The current study confers many bacterial genera which were not reported earlier in any of the shallow water vents and adds 33 new taxa to the database.
Keywords: Bacterial phylogeny; metals; novel taxa; rarefaction analysis; shallow vent

Citreicella manganoxidans sp nov., a novel manganese oxidizing bacterium isolated from a shallow water hydrothermal vent in Espalamaca (Azores) - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A Gram-stain negative, non-motile, non-spore forming, aerobic and rod or narrow lemon-shaped bacterial strain, VSW210(T), was isolated from surface seawater in a shallow water hydrothermal vent region in Espalamaca (Azores). Strain VSW210(T) was found to grow optimally at 30 A degrees C, at pH 7 and in the presence of 2-6 % (w/v) NaCl. A neighbour-joining phylogenetic tree based on 16S rRNA gene sequences revealed that strain VSW210(T) clusters with the type strain Citreicella marina CK-I3-6(T) (sequence similarity value of 99.6 %), but DNA-DNA hybridization showed DNA-DNA relatedness between the strain VSW210(T) and C. marina CK-I3-6(T) to be 55.8 +/- A 3.2 %. The DNA G+C content of strain VSW210(T) was determined to be 67.4 mol%. The cellular fatty acid profiles of strain VSW210(T) was found to contain C-18:1 omega 7c (80.1 %) and C-16:0 (9.2 %). The major polar lipids in strain VSW210(T) were identified as phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and an unidentified phospholipid. Strain VSW210(T) was found to be able to oxidize soluble Mn(II) to insoluble MnO2, which was confirmed with LBB staining. Differential phenotypic properties and genetic uniqueness revealed that this strain VSW210(T) is distinguishable from other species of the genus Citreicella. On the basis of the data presented, strain VSW210(T) is considered to represent a novel species of the genus Citreicella, for which the name Citreicella manganoxidans sp. nov. is proposed. The type strain is VSW210(T) (=KCTC 32497(T) = MCC 2286(T)).
Keywords: Azores; Citreicella manganoxidans sp nov; Hydrothermal vent; Polyphasic taxonomy; Seawater